STUDY OF THE MESOLITHIC PERIOD IN CENTRAL ASIA - Ibrokhimov Nozimjon Ikhtiyorovich; Mustafoyev Umidjon Shermatjon o'g'li (American Journals Publishing, 2025)
This article mainly discusses the climate conditions of the Mesolithic period, living conditions of that period, and the period of Mesolithic dominance in Central Asia and archaeological monuments.
Keywords: Pamir, Mesolithic, archaeologists, Ayritom, Central Fergana, Qo'shilish, nucleus, Shanidar, Central Asia, Middle East.